2022
DOI: 10.15574/sp.2022.125.19
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostics of septic myocardial dysfunction in neonates

Abstract: Neonatal sepsis (NS) continues to be the one of the major problems in neonatal practice. This is due to the variability of clinical manifestations and, in part, the lack of available diagnostic markers that are significantly associated with mortality as a result of neonatal sepsis. The purpose - to study the role of paraclinical markers of myocardial dysfunction in neonates with sepsis. Materials and methods. To achieve this goal, 87 newborns (the main group) with manifestations of a generalized infectious-inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Indicating that after delivery, general condition in neonates with sepsis was worse than the aseptic group. In agreement with our findings, Koloskova and Kretsu reported that Apgar score in the group of myocardial dysfunction in neonates with sepsis, with similar range of gestational age, was lower than in the healthy group (during the 1 st and 5 th minutes, respectively) (21) .…”
Section: Camargo Et Al Classified Eos Accordingsupporting
confidence: 93%
See 1 more Smart Citation
“…Indicating that after delivery, general condition in neonates with sepsis was worse than the aseptic group. In agreement with our findings, Koloskova and Kretsu reported that Apgar score in the group of myocardial dysfunction in neonates with sepsis, with similar range of gestational age, was lower than in the healthy group (during the 1 st and 5 th minutes, respectively) (21) .…”
Section: Camargo Et Al Classified Eos Accordingsupporting
confidence: 93%
“…They also had higher rates of hepatomegaly, lower limb edema, prolonged capillary refill time and oliguria maybe secondary to cardiac affection on top of sepsis. Camargo et al while studying complications of neonatal sepsis among similar gestational age group, found there were tachycardia in 6.5% of cases, hypotension in 21.7% and oliguria 8.6% (21) . Behairy et al found that hepatomegaly was present in more in than 60% (22) .…”
Section: Camargo Et Al Classified Eos Accordingmentioning
confidence: 97%